(untitled) (Research, Society and Development, 2022)
Agricultural soils tend to lose their quality according to their use, management and cultivation, especially in relation to the community of microorganisms present in the soil. In order to gather information on the alteration of soil microbial biodiversity due to agricultural cultivation, the objective of this bibliographic review was to use the Scopus database to verify the existing literature on the proposed theme and if there is any change according to its management. The search was carried out in the articles contained in the database, searching the title, abstract and keywords using four indexed terms: biodiversity, microbial, soil and agricultural. 891 articles were found and these were used for bibliometric analysis, for the writing of this article two filters were used: for open access articles and for the years 2017 to 2022, selecting 216 articles to be studied in this review. With the help of the statistical program R version 4.2.0, the bibliometric analysis was performed with the bibliometrix package. In the bibliometric analysis, it was possible to identify that articles related to the topic began to be published in 1992 with few publications, surpassing the mark of 25 articles published per year only in 2008, going from 75 articles published a year only in 2017 and since then. increased publication interest in the area. It was also possible to observe that the country that publishes the most on the subject is the United States and the word most cited in the titles of the articles is the bacteria microorganism. This review reveals that the change from a native system to agricultural cultivation, as well as the cultivated species, the microbial biodiversity of the soil changes.